What should be publicly funded in the Colombian health system? A mixed methods study of citizens’ perceptions - Juan Carlos Velasquez; Claudia Marcela Vélez; Diana Patricia Díaz-Hernández; Pamela Velázquez-Salazar; Gilma Hernández-Herrera; Daniel Felipe Patiño-Lugo; Olga Francisca Salazar-Blanco; Leydi Camila Rodríguez-Corredor; Viviana María Vélez-Marín; Anny Julieth Jaramillo-García (BMJ Open)
Background In recent years, citizens have become more interested and willing to influence health policy decision-making, and governments worldwide are more prone to citizen engagement in such processes. Prioritising which health technologies should be publicly funded is one decision that requires prudence and consideration of the values and expectations of the people who will be affected by it.Objective To identify and understand the citizens’ perceptions about which health technologies should be publicly funded in Colombia.Design Sequential exploratory mixed methods study; the first was a qualitative embedded case study, and the second was a Q methodology study.Participants 46 citizens were interviewed, and 30 citizens ordered a Q-sample of 45 statements.Analysis Interviews were content analysed. We performed a content analysis of the interviews, and, for the quantitative strand, we performed a principal component analysis and varimax rotation to identify view patterns. We also estimated the z-scores of each statement and the load to each factor. We jointly interpreted both sets of findings.Results We identified two general approaches citizens used to consider public funding of healthcare technologies. One approach endorsed full coverage of all health technologies required by every Colombian. In the second approach, public funding is conditional on the characteristics of the person who needs the technology, their disease/condition, the kind of technology required and the expectation of efficient health system performance. When integrating the results of the Q methodology, we found five patterns of points of view about the public funding of health technologies.Conclusion Colombian citizens consider and balance a range of different factors when making decisions about which health technologies are publicly funded. Citizens not only use technical criteria to decide but also provide the perspective and values of those affected by the decision.